Stability of grassland soil C and N pools despite 25years of an extreme climatic and disturbance regime - Wilcox, K. R.; Blair, John M.; Knapp, A. K. (My University, 2017)
Global changes are altering many important drivers of ecosystem functioning, with precipitation amount and disturbance frequency being especially important. Carbon (C) and nitrogen (N) pools are key contemporary attributes of ecosystems that can also influence future C uptake via plant growth. Thus, understanding the impacts of altered precipitation amounts (through controls of primary production inputs) and disturbance regimes (through losses of C and N in biomass) is important to project how ecosystem services will respond to future global changes. A major difficulty inherent within this task is that drivers of ecosystem function and processes often interact, resulting in novel ecosystem responses. To examine how changes in precipitation affect grassland ecosystem responses under a frequent disturbance regime (annual fire), we assessed the biogeochemical and ecological consequences of more than two decades of irrigation in an annually burned mesic grassland in the central United States. In this experiment, precipitation amount was increased by 31% relative to ambient and 1 in 3years were statistically extreme relative to the long-term historical record. Despite evidence that irrigation decreased root:shoot ratios and increased rates of N cyclingeach expected to reduce soil C and N with annual burningwe detected no changes in these biogeochemical pools. This surprising biogeochemical resistance highlights the need to explore additional mechanisms within long-term experiments concerning the consequences of global change impacts on ecosystems.
Citation: Wilcox, K. R., Blair, J. M., & Knapp, A. K. (2016). Stability of grassland soil C and N pools despite 25years of an extreme climatic and disturbance regime. Journal of Geophysical Research-Biogeosciences, 121(7), 1934-1945. doi:10.1002/2016jg003370
Keywords: Bnpp; Disturbance Regime; Global Change; Konza Prairie; Plant Community; Soil Carbon